2021
DOI: 10.1080/14760584.2021.1960161
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of the childhood vaccines: could we train the immune system against the SARS-CoV-2

Abstract: Introduction The COVID-19 pandemic is a globalized health concern caused by a beta-coronavirus named Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Since December 2019, when this outbreak flared in Wuhan, China, COVID-19 cases have been continuously rising all over the world. Due to the emergence of SARS-CoV-2 mutants, subsequent waves are flowing in a faster manner as compared to the primary wave, which is more contagious and causing higher mortality. Recently, India has emerged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…by vaccines may in this context be a double-edged sword. On one hand, it has been shown that prior vaccinations against influenza, tuberculosis and other infections may convey increased protection from COVID-19 and postulated that ongoing vaccinations against these diseases may lessen the burden of COVID-19 ( Aspatwar et al, 2022 , Debisarun et al, 2021 , O'Neill and Netea, 2020 , Sharma, 2021 ). According to the cited authors, trained immunity may act via epigenetic reprogramming of monocytes.…”
Section: Cellular Senescence Immunosenescence and Inflammaging - How ...mentioning
confidence: 99%
“…by vaccines may in this context be a double-edged sword. On one hand, it has been shown that prior vaccinations against influenza, tuberculosis and other infections may convey increased protection from COVID-19 and postulated that ongoing vaccinations against these diseases may lessen the burden of COVID-19 ( Aspatwar et al, 2022 , Debisarun et al, 2021 , O'Neill and Netea, 2020 , Sharma, 2021 ). According to the cited authors, trained immunity may act via epigenetic reprogramming of monocytes.…”
Section: Cellular Senescence Immunosenescence and Inflammaging - How ...mentioning
confidence: 99%
“…86 More recently our group has suggested the combinatorial use of childhood vaccines (BCG, MMR and OPV) along with the COVID-19 dedicated vaccines could be a potential strategy to control the COVID-19 pandemic worldwide. 87…”
Section: Covid 19 Vaccine Updatementioning
confidence: 99%
“…Vaccine-induced heterologous or nonspecific effects (known as off-target effects) can protect against pathogens other than their intended specific pathogen [16] . Vaccines, including BCG, OPV, MV, smallpox vaccine, and yellow fever vaccine, are believed to have nonspecific effects [13] . Originally, BCG was introduced to prevent TB, leprosy, and Buruli ulcer disease [13] .…”
Section: Nonspecific Protection Effects Of Bcgmentioning
confidence: 99%
“…For instance, researchers found that the SARS-CoV-2 Omicron variant (B.1.1.529) was undetectable in most participants vaccinated with mRNA-1273, BNT162b, or Ad26.COV2.S vaccines [10] , [11] . Before the COVID-19 specific vaccines were available, some existing vaccines, such as Bacille Calmette-Guérin (BCG), measles vaccine (MV), oral polio vaccine (OPV), and Measles-Mumps-Rubella (MMR), had started to be repurposed to prevent SARS-CoV-2 infection [12] , [13] . BCG is a live attenuated strain derived from Mycobacterium bovis in 1921 and has been widely used for preventing tuberculosis (TB) in children globally [5] , [14] .…”
Section: Introductionmentioning
confidence: 99%